Social Adaptation for orphans exemplar Dar Alrahmeh - Shaheen, Ezzat; Abboud, Reem; Khadour, Mazen (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aims to define the social accommodation proportion of the residents in "Dar Al-Rahma" female orphanage, using descriptive analytics approach, and its form tool. The form was distributed to a total sample of (200) inmate in the Orphanage; A positive correlation was observed between the duration of residence and the social accommodation proportion; In other words, the longer period a resident has spent, the more social accommodation proportion she has, as 80 % of the residents that spent a period "of over 6 years in the Orphanage" had a very high measure of social accommodation, while the other 20% waged between medium and weak social accommodation. Also, a negative correlation has been shown between the resident age - at the time she entered the Orphanage - and the proportion of social accommodation; In other words, the younger age a resident has entered the Orphanage, the more social accommodation she will has later; as 80 % of the residents that entered the Orphanage with "less than 3 years old" age had a very high measure of social accommodation. Moreover, a kind of correlation has been shown between the type of orphans and the proportion of social accommodation; Despite the number of full orphans ( whom have nor father neither mother FO ) is small compared to paternal or maternal orphans, but the first type ( FO ) has less chance to accommodate compared to the other types.